Palaeoenvironments and elemental geochemistry across the marine Permo‐Triassic boundary section, Guryul Ravine (Kashmir, India) and a comparison with other North Indian passive margin sections - Michael E. Brookfield; Alan G. Stebbins; Jeremy C. Williams; Wendy S. Wolbach; Robyn Hannigan; Ghulam M. Bhat (The Depositional Record, 2020)
Abstract The Guryul Permian–Triassic sediments were deposited on a passive margin in a partially enclosed basin, at a latitude of about 45°S along the southern margin of the Neotethys Ocean. The closest modern analogy is the Japan Sea rotated into a southern hemisphere orientation. Guryul element variations are subdued, mostly lithological, and take place across the change from the dominantly sandy shallow‐water Permian Zewan Formation into the dominantly shaly deeper‐water latest Permian–Triassic Khunamuh Formation, and not at the palaeontological Permian–Triassic boundary. The overall geochemistry of the Guryul sediments is very similar to that of the Ulleung Basin in the Japan Sea, where the sediments are 40%–60% eolian from loess and redeposited loess in the North China Basin. The overall Guryul geochemistry indicates that the sediments were derived from dominantly silica‐rich continental rather than silica‐poor sources although with some more silica‐poor inputs at times. Element ratios suggest increasing aridity and wind abrasion across the Permian–Triassic boundary. Various geochemical redox proxies suggest mainly oxic depositional conditions, with episodes of anoxia, but with little systematic variation across the extinction boundary. Productivity proxies suggest a slight decrease across the Permian–Triassic boundary, and at least one more decreased interval in the Early Triassic. The similar geochemistry of other localities indicate that the Guryul geochemical changes are regional in extent and representative of the North Indian Permian–Triassic passive margin. The lack of consistent element geochemical changes across the boundary accompanied by significant C, S, and other isotopic changes suggests that atmospheric and oceanic chemistry rather than physical changes, such as provenance, climate and sea‐level changes, drove the Permian–Triassic environmental changes and extinctions at least on the mid‐latitude Tethyan shelf of northern India.